Corrigendum Candidate Gene Locus for PHACE Syndrome. Am J Med Genet A. 2012;158(6):1363–1367. Doi:10.1002/ajmg.a.35341 (American Journal of Medical Genetics Part A, 2022)
Short stature is clinically and genetically heterogeneous, and defects in the extracellular matrix of growth plate cartilage represent a key disease mechanism. ACAN encodes aggrecan, the major proteoglycan of the growth plate cartilage extracellular matrix. Heterozygous ACAN variants are a recognized cause of familial short stature, often associated with advanced bone age and early growth cessation, yet they show a broad phenotypic spectrum. We aimed to delineate the clinical and molecular spectrum of ACAN-related short stature in a Turkish cohort. We retrospectively reviewed 47 individuals from 20 unrelated families with short stature (height ≤ -2 SDS) or predicted adult height < -2 SDS. Anthropometric data, dysmorphic and musculoskeletal findings, radiologic assessments, and molecular genetic results were analyzed. Among 47 individuals (20 females, 27 males), 59.6% were children. Common clinical features included a high forehead, upslanted palpebral fissures, a depressed nasal bridge, low-set anteverted ears, mild pectus deformity, and brachydactyly. Osteochondritis dissecans, early-onset osteoarthritis, and advanced bone age were identified in 6.5%, 8.7%, and 28.6% of individuals, respectively. Vertebral findings included scoliosis (19.6%), increased lumbar lordosis (13%), and vertebral endplate changes (10.9%). Genetic testing revealed 15 heterozygous ACAN variants (2 previously reported in ClinVar; 13 novel): 6 nonsense, 2 splice-site, 5 frameshift, and 2 missense. Overall, 45 patients carried pathogenic/likely pathogenic variants (14 variants), and 2 carried VUS (1 variant). ACAN-related short stature represents an important subset of familial short stature. Skeletal and musculoskeletal findings may aid diagnosis, but advanced bone age is not consistent and bone age is often appropriate for chronological age.